The Right to Good Governance Through the Lens of the Smart Cities/Municipalities Concept in the Republic of Croatia - Dujmović Bocka, Jelena; Romić, Danijela (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
The application of European principles and standards of the European Administrative Space mandates the inclusion of citizens in the creation of local policies. Citizens of the European Union have the right to be informed about the work of their local communities to understand what their local leaders are doing to improve the quality of life in these areas. This is closely linked to citizens’ right to good governance. The term "smart" implies the use of various information and communication technologies in the development of local communities. The authors begin by defining the term "smart" (what the term entails and how students perceive it). The first part of the paper focuses on defining and terminologically determining the concept of "smart," the central part presents empirical research and its findings, while the concluding section discusses and analyzes the research results. This section also offers specific proposals for enhancing the potential of individuals and the community as a whole, as well as increasing citizen engagement (through the use of digitized administrative services, smart lighting, smart transportation, smart infrastructure, environmental protection, and more). The concept of a smart city/municipality necessitates collaboration between citizens and authorities, encourages a more active lifestyle among citizens, and fosters the development of a "smart" community. The paper analyzes the management of cities/municipalities in the Republic of Croatia. The hypothesis is as follows: The role of cities/municipalities in creating smart cities/municipalities is recognized by young people who will participate in administrative processes in the future. The aim of the paper is to examine the opinions of students from the Faculty of Law in Osijek and students from the "Lavoslav Ružička" Polytechnic in Vukovar regarding their level of knowledge about the implementation of the smart cities/municipalities concept. The sample consists of students from these institutions. The research was conducted during the summer semester of the 2023/2024 academic year. The results were analyzed using descriptive statistics, and the authors believe that these findings will provide relevant stakeholders at the local level with insights into young people’s attitudes towards the development of smart city or municipality concepts. Additionally, the research results will show how young people in the Republic of Croatia perceive the implementation of such a concept, its purpose, whether it changes the governance system in local self-government, and their thoughts on potential challenges that could arise at the local level in the future. Furthermore, the study will provide the most appropriate proposals for improving this concept. It is evident that without the development of "smart" solutions, good governance of local communities cannot be achieved. Since we live in a digital age, there is a pressing need for all citizens to be educated about the purpose of developing smart cities/municipalities in order to create communities that are attractive for living to citizens worldwide. This would meet citizens’ needs and improve the efficiency of local-level operations. Local leaders should focus on creating smart solutions for financing projects related to the development of local communities.